Paleomagnetism of the Devonian Catskill Red Beds: Evidence for Motion of the Coastal New England-Canadian Maritime Region Relative to Cratonic North America ... - Kent, Dennis V.; Opdyke, Neil D. (Columbia University, 1978)
The natural remanent magnetizations of reddish clay stones, siltstones, and sandstones from the nearly flat lying Middle to Upper Devonian Catskill sequence of southeastern New York were analyzed with thermal, alternating field, and chemical demagnetization techniques. After removal of a low blocking temperature component along the present geomagnetic field direction a characteristic direction of magnetization was isolated: D = 172.3°, I = 1.0°, k = 116, and α_95 = 4.7° for N = 9 sites (43 samples), giving a paleomagnetic north pole at 46.8°N, 116.7°E, dp = 2.4°, and dm = 4.7°. The combined demagnetization analyses show this to be the only stable component of magnetization present in these rocks. The derived pole position agrees well with the poles reported for some Devonian limestones in Ohio, all falling near the Permian poles for North America, but disagrees with Devonian results from eastern Maine-New Brunswick and eastern Massachusetts which give poles at lower latitudes. A similar geographical grouping ...